(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The incidence of ophthalmologic abnormalities among the deaf children is high, compared with the hearing population of the same age. Objective:The main objective of this study was to determine the ophthalmologic abnormalities among the students attending deaf and dumb’s school in Aden city (Yemen). Methods:This was a cross sectional descriptive study carried out from October 2012 to March 2013 in a school for the deaf and dumb in Aden (Yemen). All students who consented to participate in the study, were enrolled and subjected to a detailed ophthalmic examination, including visual acuity (VA), ocular motility, slit-lamp and fundus examination conducted by a qualified ophthalmologists. Results:A total of 138 deaf students (90 males, 48 females with a male to female ratio of (2:1) were included in this study. A high proportion of the students (92; 66.6%) were in the age group >14 years. Normal eye examination was found in (51; 36.9%), ocular abnormalities found in (87; 63.1%), with some students having multiple abnormalities. Refractive errors comprised the leading abnormality in 41.3%, retinal pigment epithelium patches was found in 10.9% and Warrdenburg syndrome in 5.8%. Twelve eyes 4.4% exhibited VA < 6/18). Conclusion:Ocular abnormalities in deaf students are remarkably high which indicate the importance of early ophthalmologic examination in order to facilitate adequate integration of the deaf student as a useful and productive member in the society. Key words:Deafness, ocular abnormalities, refractory errors; visual impairment, Yemen.